THE IMPACT OF BLUE LIGHT FROM ELECTRONIC DEVICES ON VISUAL FUNCTION, CIRCADIAN RHYTHM, AND WELLBEING: A SYSTEMATIC REVIEW - Olga Żuczek,; Adam Żuczek,; Kinga Dyndał,; Marcelina Broda,; Patrycja Jędrzejewska-Rzezak,; Katarzyna Urbańska,; Izabela Szczap,; Anna Hawryluk,; Kamil Marzec,; Aleksandra Mokrzycka, (International Journal of Innovative Technologies in Social Science, 2025)
Modern lifestyles involve increasing exposure to artificial light sources, particularly from electronic devices emitting blue-enriched light. Blue light, due to its short wavelength and high photon energy, may affect retinal structures and disrupt circadian regulation, leading to sleep disturbances. Additionally, recent studies suggest that blue light exposure may influence cognitive performance, alertness, and subjective wellbeing, especially in young adults and physically active populations.The aim of this systematic review was to synthesize current evidence regarding the effects of artificial blue light on visual function, sleep quality, and human wellbeing. The review explored the underlying biological mechanisms, including the activation of melanopsin-containing intrinsically photosensitive retinal ganglion cells, and evaluated the potential risks associated with prolonged exposure to low-illuminance blue light from digital screens.Findings indicate a consistent relationship between blue light exposure and disruptions in sleep–wake cycles, with emerging data pointing toward broader psychophysiological implications. The review highlights the need for further research to better define safe exposure thresholds, assess individual sensitivity, and evaluate protective strategies such as blue light filters.